Cypro-Minoan inscriptions. Vol. 2 The corpus (Oxford: Oxford University Press, 2013)
This volume is the first comprehensive archaeological catalogue of all the extant inscriptions written in the un-deciphered syllabary of Late Bronze Age Cyprus (1500-1200 BC): the so-called Cypro-Minoan script. In conjunction with Cypro-Minoan Inscriptions Volume 1: Analysis, this volume focuses on the physical reality of the inscribed objects containing Cypro-Minoan and the archaeological contexts in which they were found. Offering a detailed, systematic, and rigorous examination of both the objects and their functions in the material record, it proposes a new way of examining the inscriptions. This comprehensive standpoint therefore considers not only the inscriptions themselves, but more importantly the contexts and functions of the inscribed objects, which are significant for the documentary evidence they bear and the part they play as physical entities manufactured, shaped, and used by past peoples for a defined purpose. Organized in a catalogue format, each object is analysed, illustrated, and accompanied by a detailed commentary on the context of recovery and typological characteristics with full bibliographical references. While a standalone reference work, it aims to showcase the inscribed objects discussed in Volume 1: Analysis, fully illustrating them in a series of photographs, including 50 colour plates, and drawings.
PREFACE AND ACKNOWLEDGEMENTS ; LIST OF ABBREVIATIONS ; LIST OF ILLUSTRATIONS AND PLATES ; INTRODUCTION: AN ARCHAEOLOGICAL CORPUS ; 1.1 Historical Background ; 1.2 Definition of the Corpus ; 1.3 Corpus Structure and Order of Entry ; 1.4 Additions (ADD ##218-##243) ; 1.5 Appendices ; THE INSCRIPTIONS: ##001-##243 ; APPENDICES ; List of Cypro-Minoan Objects and their Functions ; Sign Variants ; GENERAL BIBLIOGRAPHY.
Includes bibliographical references.
Keywords: Inscriptions, Cypro-Minoan; European Union -- Civilization -- Cyprus; European history: BCE to c 500 CE; History / Ancient / General; Social science -- Archaeology; Inscriptions, Cypro-Minoan; Ancient Greece ; Prehistory